2017
DOI: 10.1126/science.aal3439
|View full text |Cite
|
Sign up to set email alerts
|

Identification of single-site gold catalysis in acetylene hydrochlorination

Abstract: Gold-on-carbon catalysts are analogs of homogeneous gold catalysts that use a redox couple of Au(I) and Au(III) species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

17
405
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 417 publications
(444 citation statements)
references
References 43 publications
(41 reference statements)
17
405
1
Order By: Relevance
“…Monitoring the changes in white line height, a feature detectable in the XANES region which corresponds to the Au 2p 3/2 → 5d primary transition (see experimental section for more details), showed that while heating the catalyst to the reaction temperature (200°C) under Ar, the Au(III)/Au(I) ratio significantly changed from Au(III) chloride to Au(I) chloride (Figure 1b). 9 Therefore, while it is true to state single-site cationic species are retained on…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Monitoring the changes in white line height, a feature detectable in the XANES region which corresponds to the Au 2p 3/2 → 5d primary transition (see experimental section for more details), showed that while heating the catalyst to the reaction temperature (200°C) under Ar, the Au(III)/Au(I) ratio significantly changed from Au(III) chloride to Au(I) chloride (Figure 1b). 9 Therefore, while it is true to state single-site cationic species are retained on…”
Section: ■ Introductionmentioning
confidence: 99%
“…9 Analysis of the Au L 3 -edge X-ray absorption near-edge structure (XANES) and the extended X-ray absorption fine structure (EXAFS) showed the operating catalyst comprised of atomically dispersed cationic species with no Au nanoparticles being present in the most active Au/C catalysts. During the reaction, distinct changes in the XANES were observed, which clearly correlated to the catalyst productivity, showing that the active catalysts were comprised of atomically dispersed cationic gold in both Au(III) and Au(I) oxidation states.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously highlighted the work of LezcanoGonzalez et al (2016), which combines high-resolution fluorescence-detection X-ray absorption near-edge spectroscopy, X-ray diffraction and X-ray emission spectroscopy under operando conditions to provide detailed new insights into the nature of the Mo species on zeolite ZSM-5 during methane dehydroaromatization. Another recent example is the work of Malta et al (2017), who combined XAFS and modelling to show that in an industrially important acetylene hydrochlorination catalyst, comprising gold on a carbon support, the active sites are not, as previously thought, gold nanoclusters but single gold ions. Catalysis will unquestionably continue to pose fascinating problems for structural science.…”
mentioning
confidence: 99%